2015
DOI: 10.3389/fmicb.2015.01270
|View full text |Cite
|
Sign up to set email alerts
|

Degradation Network Reconstruction in Uric Acid and Ammonium Amendments in Oil-Degrading Marine Microcosms Guided by Metagenomic Data

Abstract: Biostimulation with different nitrogen sources is often regarded as a strategy of choice in combating oil spills in marine environments. Such environments are typically depleted in nitrogen, therefore limiting the balanced microbial utilization of carbon-rich petroleum constituents. It is fundamental, yet only scarcely accounted for, to analyze the catabolic consequences of application of biostimulants. Here, we examined such alterations in enrichment microcosms using sediments from chronically crude oil-conta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 35 publications
(74 reference statements)
1
6
0
Order By: Relevance
“…They were recovered from clone libraries created from two chronically polluted marine sediment samples, an acidic beach pool, and the P. oleovorans genome (see the legend to Table S1) (1618). This means a ratio of circa 1 positive result per 50,000 clones tested; note that this ratio is an indicator of the abundance of enzyme activities in metagenomes (5, 19).…”
Section: Resultsmentioning
confidence: 99%
“…They were recovered from clone libraries created from two chronically polluted marine sediment samples, an acidic beach pool, and the P. oleovorans genome (see the legend to Table S1) (1618). This means a ratio of circa 1 positive result per 50,000 clones tested; note that this ratio is an indicator of the abundance of enzyme activities in metagenomes (5, 19).…”
Section: Resultsmentioning
confidence: 99%
“…The lack of nitrogen and phosphorus in marine environments is one of the main factors negatively affecting the growth of HC-degrading bacteria in polluted sites. Recently, the use of uric acid as a natural fertilizer for the bioremediation of marine oil pollution has been proposed to overcome this limitation (Ron and Rosenberg, 2014) and a microcosm-scale study showed its rapid conversion to ammonium and a role in the selection of microbial communities encompassing known hydrocarbonoclastic bacteria (Bargiela et al, 2015b;Gertler et al, 2015). Four of the tested isolates (one A. borkumensis and three M. hydrocarbonoclasticus) were capable to degrade uric acid suggesting their potential to be responsive to uric acid amendment in bioremediation trials.…”
Section: Discussionmentioning
confidence: 99%
“…Increasing microbial degradation of BTX by bioaugmentation (increasing the number of degraders) and biostimulation (addition of stimulative nutrients) are novel strategies (Bargiela et al 2015). As it was observed that bacteria preferentially attack on simpler carbon sources (hydrocarbons), addition of stimulative/enhancer carbon sources leading to higher degradation seems to be good strategy.…”
Section: Microcosm Studiesmentioning
confidence: 99%
“…Nutrient-enhanced bioremediation is effective only up to a point (Singh et al 2015). Bargiela et al (2015) showed the use of nitrogen sources could work as biostimulant and increase the BTX degradation in microcosms. Biostimulants affected the initial microbial communities and re-organized the microbial taxa on the basis of metabolic abilities of both BTX degradation and the biostimulants used.…”
Section: Microcosm Studiesmentioning
confidence: 99%
See 1 more Smart Citation